Pheochromocytoma Presenting As Acute Myocardial Infarction - Jayaprasad, N; Madhavan, Suresh (Nepalese Heart Journal, 2015)
Pheochromocytomas are rare neuro-endocrine tumors arising from chromaffin cells of the sympathetic nervous system.Pheochromocytomacan have diverse clinical presentations, which makes the diagnosis often difficult. We present a case of adrenalpheochromocytoma presenting as acute ST elevation myocardial infarction (STEMI). Catecholamine surge in patients with pheochromocytoma can cause myocardial infarction in the absence of atherosclerotic coronary artery disease. Pheochromocytoma presenting as acute myocardial infarction is very rare and it occurs in young individuals. This is a rare case report of pheochromocytoma in an elderly male presenting with acute STEMI successfully treated by resection of tumor. Nepalese Heart Journal 2015;12(2):89-92